2014
DOI: 10.1097/dbp.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization of Autism in the Latino Community and its Relationship With Early Diagnosis

Abstract: Objective Early identification of autism spectrum disorders (ASD) has been linked to improved long-term developmental outcomes. However, Latino children are diagnosed later than white non-Latino children. We aimed to qualitatively assess the understanding and conceptualization of ASD in the Latino community in order to understand potential community barriers to early diagnosis. Method We conducted 5 focus groups and 4 qualitative interviews with 30 parents of typically-developing Latino children in Oregon. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 27 publications
4
55
0
3
Order By: Relevance
“…In particular, families of lower socioeconomic status may know less about genetics, and/or health care and educational providers may also provide less information about genetics to these families when discussing ASD. Overall, our results support prior reports suggesting that family socioeconomic background may play an important role in how families interpret their child’s developmental problems (Mandell & Novak, 2005; Zuckerman et al, 2014). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, families of lower socioeconomic status may know less about genetics, and/or health care and educational providers may also provide less information about genetics to these families when discussing ASD. Overall, our results support prior reports suggesting that family socioeconomic background may play an important role in how families interpret their child’s developmental problems (Mandell & Novak, 2005; Zuckerman et al, 2014). …”
Section: Discussionsupporting
confidence: 90%
“…However, parental beliefs regarding the cause of pediatric conditions are relevant, as these beliefs may affect how parents communicate with providers. For instance, if parents do not see ASD as a medical condition, they may be less likely to view the child’s diagnosis in a medical context, and therefore be less likely to raise it with medical staff (Zuckerman et al, 2014). Parental beliefs might also alter how parents view their child overall as well as their own personal roles or responsibilities for his/her condition.…”
Section: Introductionmentioning
confidence: 99%
“…Several mothers stated that the paperwork was provided to them in English; and furthermore, their doctors did not speak Spanish. This is similar to other research where language is a barrier [Mandell & Novak, 2005;Zuckerman et al, 2013;Zuckerman et al, 2014aZuckerman et al, , 2014b.…”
Section: Discussionsupporting
confidence: 90%
“…Some authors have suggested that some families, by virtue of their ethnicity, are less familiar with the early manifestations of ASD200 or ascribe a different meaning to atypical behaviors or late milestones within their cultural context,201 and that this may contribute to delays in diagnosis. However, other studies have examined the broader context by which ethnicity and cultural matters may contribute to variations in care and lived experience in relation to the diagnosis of ASD.…”
Section: Family Preferences For Asd Diagnostic Assessmentmentioning
confidence: 99%